DETERMINING THE EFFICIENCY INDICATORS OF THE NEWLY ESTABLISHED FIRM TECHNICAL SERVICE POINT - Rustamov Rakhmatali Muradovich; Kholmirzaev Ilkhom Alohanovich (Modern American Journals, 2025)
The reliable operational condition of traction units plays a decisive role in the efficiency of agricultural production processes. During autumn and summer plowing seasons, the occurrence of technical failures in field machinery often leads to delays in agrotechnical operations, a decrease in soil moisture, the formation of large soil clods, and ultimately a reduction in overall crop yields. Therefore, the technical readiness of machinery and the promptness of maintenance services represent critical factors influencing the quality and timeliness of agricultural activities.
Keywords: Traction units, maintenance service, failure statistics, service points, plowing efficiency.